The use of spectrum auctions to attain multiple objectives: Policy implications. Issue 5 (June 2017) - Cave, Martin; Nicholls, Rob
Abstract: The first spectrum auctions generally assigned the chosen number of licences of predetermined size to the highest bidders, but auctions now allow a greater choice of outcomes, with bidders with existing spectrum portfolios competing, with others, for multiple lots, often in different bands. Modern auctions also contain design features expressly directed at efficiency and equity objectives. In relation to efficiency, spectrum caps or set asides for new entrants can be incorporated to combat the exercise of market power downstream. In relation to equity objectives, licence conditions may specify obligations to provide coverage in non-commercial areas, or promises of the attainment of social objectives can be given a weighting, with revenue, in the determination of winning bids. The paper provides and overview of the wide use of such tools and the consequences for the operation of the auction process. Some lessons are drawn for future spectrum auctions.